Self-help materials for the prevention of smoking relapse: study protocol for a randomized controlled trial. - Song, F; Holland, R; Barton, G; Bachmann, M; Blyth, A; Maskrey, V; Aveyard, P; Sutton, S; Leonardi-Bee, J; Brandon, T (BioMed Central, 2012)
BACKGROUND: Most people who stop smoking successfully for a few weeks will return to smoking again in the medium term. There are few effective interventions to prevent this relapse and none used routinely in clinical practice. A previous exploratory meta-analysis suggested that self-help booklets may be effective but requires confirmation. This trial aims to evaluate the effectiveness and cost-effectiveness of a set of self-help educational materials to prevent smoking relapse in the National Health Service (NHS) Stop Smoking Service. METHODS/DESIGN: This is an open, randomized controlled trial. The target population is carbon monoxide (CO) verified quitters at four weeks in the NHS stop smoking clinic (total sample size N = 1,400). The experimental intervention tested is a set of eight revised Forever Free booklets, including an introduction booklet and more extensive information on all important issues for relapse prevention. The control intervention is a leaflet that has no evidence to suggest it is effective but is currently given to some patients using NHS stop smoking services. Two follow-up telephone interviews will be conducted at three and 12 months after the quit date. The primary outcome will be prolonged abstinence from months four to 12 with no more than five lapses, confirmed by a CO test at the 12-month assessment. The secondary outcomes will be seven-day self-report point prevalence abstinence at three months and seven-day biochemically confirmed point prevalence abstinence at 12 months. To assess cost-effectiveness, costs will be estimated from a health service perspective and the EQ-5D will be used to estimate the QALY (Quality Adjusted Life Year) gain associated with each intervention. The comparison of smoking abstinence rates (and any other binary outcomes) between the two trial arms will be carried out using odds ratio as the outcome statistic and other related statistical tests. Exploratory subgroup analyses, including logistic regression analyses with interaction terms, will be conducted to investigate possible effect-modifying variables. DISCUSSION: The possible effect of self-help educational materials for the prevention of smoking relapse has important public health implications. TRIAL REGISTRATION: Current Controlled Trials ISRCTN36980856.